In a democracy, what makes an external self-determination claim reasonable? Some reflections on the moral aspect of the question - Vergés, Joan (Las Torres de Lucca. International Journal of Political Philosophy, 2021)
The central part of this article deals with the morality of secession. We present the three main "pure" theories about the morality of secession and suggest the greatest justifying power of an "impure" or mixed theory. At the same time, however, we advocate the need for a proper understanding of the question of the morality of secession. More specifically, we suggest that the best way to raise it is by introducing the notion of "reasonableness" into the question itself.